Conceptualizing perceived brand globbiness vs localness: Insights into Malaysian consumer preferences and purchase intentions - Masran Tamin; Faerozh Madli; Suddin Lada; Nizhamuddin AB; Tinik Sugiati; Dean Nelson Mojolou (RSIS International, 2025)
As globalization intensifies and spreads, it becomes important for marketers to appreciate the way consumers perceive global and local brands. This study seeks to assess the impact of Perceived Brand Globbiness (PBG) and Perceived Brand Localness (PBL) towards brand trust, brand equity and purchase intention amongst Malaysian consumers. This study will employ Signaling Theory, the Consumer Based Brand Equity (CBBE) Model, and the Theory of Planned Behavior (TPB) to develop a conceptual framework to address these relations. The study uses quantitative research methods adopting purposive sampling techniques to engage 200 Malaysian consumers who purchase both global and local brands on a regular basis. Data analysis will be conducted in understanding the relationship between the variables. The findings are expected to indicate the factors that brand trust, brand equity and purchase intention in global versus local brand perception. This study will be beneficial to marketers in formulating plans that meet both local and global perspectives. The research provides the theoretical basis for the understanding of branding in pluralistic and developing market settings.